Wind-tunnel study of exhaust-intake cross contamination and dispersion of rooftop emissions, Hospital of the University of Pennsylvania: HUP phase IV - Peterka, J. A. (Jon A.), author; Cermak, Jack E., author; Fluid Mechanics and Wind Engineering Program, Fluid Dynamics and Diffusion Laboratory, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1984)
A wind-tunnel study on a 1:250 scale model of a planned Phase IV addition to the Hospital of the University of Pennsylvania complex and the nearby structures was completed in the Fluid Dynamics and Diffusion Laboratory at Colorado State University. The study was accomplished to determine the concentration of effluents, emitted from various exhausts near and on the proposed addition, at various air intakes and other critical locations. Tracers emitted from individually modelled sources were sampled at 47 receptors for each of eight wind directions to measure the extent of exhaust-intake cross-contamination and dispersion of roof-top emissions. Some "follow-on" tests were also performed with a modified model to determine effluent concentrations at the HUP IV penthouse from selected nearby sources. Additional wind-tunnel testing included velocity measurements to determine mean and gust winds at selected locations in the vicinity of the Hospital. The pedestrian-level wind data were recorded at 18 different locations for each of 16 wind directions. Selected test conditions were identified for inclusion in a visualization study. Visible smoke plumes, generated at locales of special interest, were recorded on VHS format video cassettes. The concentration data revealed that the complex contains regions where the air is relatively stagnant. Exhaust gases in these regions experience little, if any, sweeping action from the wind, from any direction, to enhance dispersion. Some interaction between area exhausts and intakes situated on the Phase IV addition, was measured. Any adverse contamination of intake air is dependent upon composition of the exhaust effluents. The velocity measurements indicated that the new structure should not induce any significant wind related problems for pedestrian traffic in the surrounding area.
CSU Project 2-95750.
For Hospital of the University of Pennsylvania, Philadelphia, Pennsylvania.
CER84-85JEC-JAP1.
CER84-85JEC-JAP1a (Appendices).
Keywords: Philadelphia (Pa.) -- Buildings, structures, etc.; Wind tunnel models; Buildings -- Pennsylvania -- Philadelphia -- Aerodynamics